In‐Situ Upgrading of Coal Pyrolysis Tar with Steam Catalytic Cracking over Ni/Al2O3 Catalysts. Issue 16 (24th April 2020) - Cao, Siqian; Wang, Dechao; Wang, Mingyi; Zhu, Jialong; Jin, Lijun; Li, Yang; Hu, Haoquan
Abstract: In‐situ upgrading of coal pyrolysis tar with steam catalytic cracking (SCC) is a promising technique to improve tar quality. In this study, Ni/Al2 O3 catalysts with different Ni contents were used for in‐situ SCC of coal pyrolysis tar at 650 °C. The results showed that Ni/Al2 O3 catalysts can enhance the water conversion and light tar yield. Both SCC and tar catalytic cracking can occur simultaneously over Ni/Al2 O3, and the free radicals produced by tar catalytic cracking can be stabilized by active species generated from SCC to avoid excessive cracking of tar and improve light tar yield. 4Ni/Al2 O3 (4 wt. % Ni) exhibits the best performance, contributing to the highest water conversion of 4.74 wt. % and light tar yield of 11.90 wt. %, respectively. Correspondingly, the content of light fraction (boiling point less than 360 °C) in tar sample increases from 48.0 wt. % to 67.0 wt. %, and the average molecular weight decreases from 353 amu to 253 amu over 4Ni/Al2 O3 . This is consistent with the increase of benzenes, phenols and naphthalenes and the decrease of long‐chain aliphatic hydrocarbons, 3‐ and 4‐ring aromatics in upgraded tar. In addition, the higher ratio of uncondensed aromatic protons to condensed aromatic protons in upgraded tar reveals the fact that 4Ni/Al2 O3 can promote ring‐opening reaction of PAHs, which can well interpret the tar upgrading process. Abstract : Ni/Al2 O3 catalyst promotes in‐situ catalytic cracking of the heavy components in coal pyrolysis tar into small molecular tar fragments, which combines with the active hydrogen and hydroxyl generated by the steam over Ni/Al2 O3 to generate more light tar.